How do you solve #(x-1) /3 - (x-1) /2 = 6#?

1 Answer
Feb 24, 2016

Answer:

# x = - 35 #

Explanation:

The easiest method to use to solve equations of this form is to use a common denominator, which in this case is 6. Multiply each individual term in the equation by 6 and then simplify the equation and solve for x.
# 6( ( x - 1)/3) - 6( ( x - 1 )/2) = 6( 6 )#

#2( x - 1 ) - 3( x - 1) = 36#

#2x - 2 -3x + 3 = 36#

# -x + 1 = 36 #

# -x = 35#

# x = -35#

Check this answer by substituting -35 in for x in the original equation.

# (-35 -1)/3 - ( -35 -1)/2 = 6#

# -36/3 - -36/2 = 6#

# -12 + 18 = 6#

# 6 = 6 #